A - Solomon, Robert C. (Oxford University Press, 1996)
In this accessible and comprehensive work, Robert Solomon and Kathleen Higgins cover the entire history of philosophy--ancient, medieval, and modern, from cultures both East and West--in its broader historical and cultural contexts. Major philosophers and movements are discussed along with less well-known but interesting figures. The authors examine the early Greek, Indic, and Chinese philosophers and the mythological traditions that preceded them, as well as the great religious philosophies, including Christianity, Hinduism, Judaism, and Taoism. Easily understandable to students without specialized knowledge of philosophy, A Short History of Philosophy demonstrates the relevance of philosophy to our times, illuminating the impact of the revolutions wrought by science, industry, colonialism, and sectarian warfare; the two world wars and the Holocaust; and the responses of philosophy in the schools of existentialism, postmodernism, feminism, and multiculturalism. In addition, the authors provide their own twists and interpretations of events, resulting in a broad view of the nature of philosophy as an intellectual discipline and its sometimes odd and dramatic consequences